The Influence of Competence and Talent Management on Employee Performance in SMEs in Cimahi: An Empirical Analysis - Galih Raspati; Umban Adi Jaya; Firly Agustiansyah; Theodora Zanetha Yovitasari; Diah Pitaloka (The Eastasouth Management and Business, 2026)
This study aims to investigate the impact of competencies and talent management on employee performance in Micro, Small, and Medium Enterprises (MSMEs) in Cimahi City, highlighting the urgency of enhancing employee performance for organizational sustainability and growth. An explanatory survey method with a verificative approach was employed, involving a sample of 89 employees from a population of 117 MSMEs, selected using the Krejcie and Morgan table. Data analysis was conducted through multiple regression using SPSS 25 to explore the relationships between competencies, talent management, and employee performance. The findings reveal that both competencies and talent management positively and significantly affect employee performance, with a 0.421 unit increase in performance for each unit increase in competencies and a 0.408 unit increase for talent management. The urgency of this research lies in its potential to improve employee performance through effective competencies and talent management, helping MSMEs overcome challenges, contribute to local economic growth, and provide a foundation for policies that support MSME development, thereby promoting sustainability and job creation. This study underscores the importance of implementing robust competencies and talent management strategies to achieve optimal and sustainable performance in MSMEs.